(untitled) (INNOVATIVE ECONOMY, 2023)
Shmyhel O.Ye. MODERNIZATION OF ACCOUNTING IN THE CONTEXT OF THE MODERN DEVELOPMENT OF THE DIGITAL ECONOMY Purpose. The aim of the article is to substantiate the need for the development of digitalization of modern accounting of companies. Methodology of research. The research was conducted using a dialectical approach to the study of the current state of development of the digital economy. General scientific and special methods were used in the article, in particular: analytical - when reviewing normative sources; monographic - when studying literary sources on digitalization of accounting; system and analytical - when processing the received information. Findings. It was determined that in the conditions of digitalization of business processes, implementation and development of new business concepts, approaches to the methodology of accounting are changing, the need to create a new concept of accounting in companies under the auspices of total digitalization is increasing. It is substantiated that digitization and robotization contribute to changes in the functioning of company management and accounting, in particular. It was revealed that the result of the development of digital technologies will be the optimization of the organizational structure and management services of the accounting department, including due to the reduction of the staff and the review of the functionality, the introduction of new information and technological systems for processing primary documents and information, the modernization of accounting processes and accounting policy in general; strengthening requirements for professional skills of users. Originality. Directions for the development of robotization in the context of digitalization of the company’s accounting service are proposed. The implementation of robotization in the activities of the accounting service of companies is substantiated. Practical value. The obtained research results will contribute to increasing the effectiveness of the formation and development of accounting robotization in the conditions of the digital economy and will become the basis for further scientific developments in this field. Key words: accounting, modernization, digitization, robotics, information technologies, business process.